INFLUENCE OF F CONTENT ON THE COMPOSITION OF AL-RICH SYNTHETIC PHLOGOPITE: PART II. PROBING THE STRUCTURAL ARRANGEMENT OF ALUMINUM IN TETRAHEDRAL AND OCTAHEDRAL LAYERS BY... - Fechtelkord M.; Behrens H.; Holtz F.; Bretherton J.L. (My University, 2003)
The influence of F substitution on the local structure of Al in the tetrahedral and octahedral sheets of synthetic Al-rich phlogopite samples with nominal gel compositions of K(Mg3-xAlx)[Al1+xSi3-xO10] (OH)y(F)2-y between 0.0 ≤ x ≤ 0.8 and 0.5 ≤ y ≤ 1.8, was studied by 27Al MAS, MQMAS, [1H/19F] → 27Al 2D CPMAS (HETCOR) and [1H/19F] → 27Al REDOR solid-state NMR and by IR spectroscopy. Changes in intensity of the absorption bands in the OH-stretching region of the IR spectra clearly indicate the incorporation of octahedral Al. Signals from the different phases can be separated in the 27Al MQMAS NMR spectra by generation of an isotropic dimension in F1. The 27Al quadrupolar parameters of the four phases were estimated from 27Al MAS NMR spectra obtained at 104.26 and 208.42 MHz. The quadrupolar coupling constant and isotropic chemical shift increases with increasing Al content for the IV Al site in phlogopite. The VI Al site shows a clear increase of the asymmetry parameter and CQ with increasing F content. The estimated 27Al signal areas show the lowest amount of impurity phases at high OH contents and a stabilization of VI Al sites by hydroxyl groups. The [1H] → 27Al 2D CPMAS (HETCOR) NMR experiment at short contact times provides information about site neighborhoods of tetrahedral Al sites and Mg3OH as well as Mg2AlOH sites, whereas magnetization is only transferred to the octahedral Al sites from hydroxyl groups in Mg2AlOH sites. The [19F] → 27Al 2D CPMAS (HETCOR) NMR spectrum is dominated by IV Al sites coupled to the Mg3F complex in phlogopite. Resonances from Mg2AlF complexes are not observed. Finally, the [1H/19F] 27Al REDOR experiments support the results of the 2D CPMAS (HETCOR) experiments.
Keywords: MINERALOGY; STUDIES; phlogopite